Knowledge of the senior high-school students in Sukarami subdistrict of Palembang about dental radiographic examination - Kartika, Dewi; Manja, Cek Dara; Heliza, Vini (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2024)
Objectives: The study on knowing lay-persons’ radiographic examination is still rare. It actually can provide the description of how far they understand it in dentistry, especially in dentistry’s radiography. This research is aimed to find out the senior high school students’ level of knowledge about dental radiographic examination. Materials and Methods: This research used a descriptive survey method with a cross-sectional design. The population was the grade XII students of SMA 13, Palembang, and 174 of them were used as the samples, taken by using purposive sampling technique and was in accordance with the inclusion and exclusion criteria, using Google form questionnaire, and analyzing descriptively. Results: The result showed that 23 respondents (13.22%) had good knowledge, 108 respondents (62.07%) had moderate knowledge, and 43 respondents (24.71%) had poor knowledge. Conclusion: The students’ level of knowledge at SMA 13 Palembang high school about dental radiographic examination was moderate.